Penilaian Kinerja Keuangan Berdasarkan Analisis Rasio Keuangan (Studi pada BMT Amanah Banjarmasin) - Syafril Syafril (Akuntabilitas, 2020)
Research used to know financial performance and compared with industry standards. Focus on this BMT Amanah Banjarmasin and compared with Bank Indonesia standards. Focus on this research is on a financial report 2017 and 2018. From the BMT financial statements then analyzed the liquidity, solvency, rentability, and effectivity for comparison of results in each year and will be adjusted to Bank Indonesia (BI) standard that can be analyzed to measure what the financial level and performance of the BMT . Data analysis method is comparative descriptive analysis. While the data source used in this study is secondary data in the form of bank financial statement documents. The results show, bank liquidity is able to meet the short term in a timely manner. The result of solvency is seen ability of bank in fulfilling and keeping its ability to always able to fulfill its obligation in paying debt in a timely manner. The profitability of banks has a good ratio. Maximally maximized resource viewing effectivity results.